Vivipary in litchi (Litchi chinensis) : new report (Current Horticulture, 2024)
Litchi (Litchi chinensis Sonn.), Sapindaceae family, is an evergreen subtropical fruit tree. A study was carried out at ICAR-NRC on Litchi, Muzaffarpur, during 2017-18 to assess the occurrence of vivipary in 600 open seedling populations. Based on morphological characters, 82 promising genetic stocks were identified and vegetatively propagated, and planted in the field in 2014 for further evaluation. Vivipary can be divided into two major different forms, viz. true vivipary and crypto vivipary. Litchi showed crypto vivipary in which zygotes significantly develop but do not penetrate the pericarp before dispersal.The fruits of litchi NRCL-29, when cut and exposed the seed, the germinated seeds inside fruit were found very clearly. Out of these, NRCL-29 exhibited most precocious for flowering and fruiting on account of third year of planting. However, stress can induce flowering and fruiting in younger plants.